Geology and Sedimentology of Transect I – East Face, Central Gunung Semanggol, Bukit Merah, Perak - Jing Hang , Eric Teng (Universiti Teknologi PETRONAS, 2016)
Gunung Semanggol is part of the Semanggol Formation that extends from north and south Kedah. There is less publication on the general geology of Gunung Semanggol compare to the Semanggol Formation in Kedah, despite the named “Semanggol” are taken from the mountain range. This project will focus on the geology and sedimentology of Gunung Semanggol, by focusing on the East face of Central Gunung Semanggol, Transect-1. Detail observation and data collection will be done and recorded in the study area. 3 major facies observed in the field, namely black shale facies, interbedded siltstone and mudstone facies and sandstone facies. Detail sedimentary logging created on each outcrop shows the younging direction is towards East and the facies are interpreted to be Rhythmite Member with overall coarsening upward trend. Structural study show the major stress direction is West-East trending and sedimentary dipping towards South-East direction. From the stratigraphical analysis, the possible deposition environment for Gunung Semanggol is probably to be in the outer shelf margin instead of deep marine setting. The sedimentary distributions of study area are illustrated by the geological map and cross section produced.